Identification and characterization of OXA-48 producing, carbapenem-resistant Enterobacteriaceae isolates in Turkey - Kilic, Abdullah; Aktas, Zerin; Bedir, Orhan; Gumral, Ramazan; Bulut, Yasemin; Stratton, Charles; Basustaoglu, A. Celal (My University, 2011)
Carbapenem resistance in Enterobacteriaceae isolates has been reported from Turkey and is most often mediated by OXA-48 type carbapenemases. We report the identification and characterization of four carbapenem-resistant isolates (three Klebsiella pneumoniae and one Escherichia coli) among 515 clinical Enterobacteriaceae isolates collected during a 7-month study period in Ankara, Turkey. The four isolates were recovered from blood and urine specimens in patients with varied clinical manifestations. They had distinct pulsed-field gel electrophoresis patterns and harbored a variety of ?-lactamases including bla TEM-1, bla SHV-12 genes, bla SHV-11, and/or bla CTX-M-15. PCR and sequencing analysis revealed that the bla OXA-48 gene was present in all four isolates. Our data indicated that the OXA-48-type carbapenemase was the only mechanism for carbapenem resistance in our hospital. © 2011 by the Association of Clinical Scientists, Inc.
Keywords: Antibiotic resistance; Carbapenemase; Enterobacteriaceae; OXA-48